Analysis Of The Meaning And Function Of Character Education Values In Javanese Proverbs: Semantic Study - Kalina Dewantara Putri; Endang Setyowati (UIBU, 2024)
Semantics is a branch of linguistics that studies the meaning of language. This study focuses on analyzing the meaning, function, and values ​​of Character Education contained in Javanese proverbs. The objectives of this study are: (1) to describe the values ​​of Character Education contained in Javanese proverbs, (2) to find out the meaning of the values ​​of Character Education contained in Javanese proverbs, (3) to find out the function of the values ​​of Character Education contained in Javanese proverbs. The research method used in this study is the descriptive method. The descriptive method is a method that describes or presents data obtained from researchers. The data for this study comes from a book of Javanese proverbs. The data used in this study is secondary data, because it is in the form of words found in the book of Javanese proverbs. The data collection technique in this study is the listening and recording technique. The data analysis used in this study is interactive data analysis. The method for presenting the results of data analysis in this study uses the informal presentation method. This informal presentation is done by presenting the results using words. From the results of data analysis, it can be seen that the expressions contained in Javanese proverbs have 9 values ​​of character education, including: (1) 5 religious, (2) 5 honest, (3) 2 fond of reading, (4) 4 hard work, (5) 1 independent, (6) 4 love peace, (7) 1 appreciate achievement, (8) 1 tolerance, (9) 2 responsibility. The analysis of semantic meaning in Javanese proverbs includes 52 words of lexical meaning analysis, 27 words of grammatical meaning, and 4 words of non-referential meaning. Therefore, the results of this study are expected to be used as an initial reference for researchers who are interested in deepening more about literary research, especially Javanese Proverbs and Character Education